Pharmaceutical Applications of Glucose Syrup from High Quality Cassava Flour in Oral Liquid Formulations. (24th January 2022) - Simpson, Ivan K.; Owusu, Frederick W. A.; Boakye-Gyasi, Mariam E.; Entsie, Philomena; Bayor, Marcel T.; Ofori-Kwakye, Kwabena
Abstract : Pharmaceutical oral solutions are preparations in which the active ingredients are dissolved in suitable liquid vehicles such as syrups. This study sought to determine the potential of glucose syrup produced from high quality cassava flour (HQCF) as a vehicle or sweetener in the preparation of paracetamol syrup and simple linctus. Four formulations (two paracetamol syrups (B1 and B2) and two simple linctus formulations (A1 and A2)) were prepared using glucose syrup from HQCF as vehicle or sweetener while two controls (B3 and A3) were prepared for each group using sucrose syrup as vehicle or sweetener. Two brands of paracetamol syrup and simple linctus were purchased from retail pharmacies to serve as standards. Physical and organoleptic parameters such as pH, taste and color, microbial load, and drug content of all formulations were determined. All formulations passed the microbial load and drug content tests as specified by the British Pharmacopoeia. The paracetamol syrups were all sweet with characteristic bitter aftertastes except formulation B2 which was sweetened with sucralose. All the simple linctus formulations were sweet except A2 (sweetened with sucralose) which was very sweet. The taste masking capacity of the glucose syrup produced from HQCF matched that of the sucrose syrup in the products formulated. Therefore, glucose syrup from HQCF could be a suitable alternative to sucrose syrup as a vehicle or sweetener in oral liquid formulations and can ultimately reduce the cost of these oral liquid formulations.